TRENDS IN UNMET NEED FOR FAMILY PLANNING 1990 – 2018: ITS CORRELATION WITH SOCIO-DEMOGRAPHIC INDICES AND MODERN CONTRACEPTIVE PREVALENCE RATES IN NIGERIA. - Audu Alayande; Yusuf Bello; Lanre Bajowa; Elvis Evborein; Islamiyah Alayande Nuhu; Gregory Umeh (Journal of Community Health and Preventive Medicine, 2023)
This is a desk review of the past Demographic and Health Surveys (1990 - 2018) to provide information on the trends in Unmet Need for Family Planning and its relationship with socio-demographic variables, women empowerment and Gender Based Violence. These variables were cross-tabulated using USAID statcompiler and the findings were presented on tables of trends. Although, the unmet need is highest amongst women in urban areas, in the southern part of the Country, those with primary education and women in the fourth wealth quintile. There is no clear trend relationship between unmet need for family planning and women decision making, the reasons for wife beating and modern contraceptive prevalence rate (mCPR). The lack of consistent trend relationship between unmet need and some of the socio-demographic variables call for further in-depth surveys to understand the direct and indirect factors which determines individual and couples’ fertility preference and the need for contraception.